Significant barriers to diagnosis and management of adrenal insufficiency in Africa - Thabiso R P Mofokeng; Salem A Beshyah; Fazleh Mahomed; Kwazi C Z Ndlovu; Ian L Ross (Endocrine Connections, 2020)
Background: The burden and management of primary adrenal insufficiency (PAI) in Africa have not been well documented. We aimed to identify specific dis ease characteristics, patient demographics, and patterns of clinical management in es tablished PAI in Africa. Methods: An online survey of physicians’ experience relating to PAI. Results: There were 1334 responses received, 589 were complete, and 332 respondents reported managing patients with hypoadrenalism. The described responses were related to a calculated pool of 5787 patients with hypoadrenalism (2746 females, 3041 males), of whom 2302 had PAI. The likely causes of PAI in Sub-Saharan Africa (SSA) vs the Middle East and North Africa (MENA) regions included aut oimmune disease (20% vs 60.3%; P < 0.001), tuberculosis (34% vs 4.1%; P < 0.001), AIDS (29.8% vs 1%; P < 0.001), malignancy, and genetic conditions. Sixteen percent of AD patie nts (376/2302) presented in an adrenal crisis. Medical emergency identification was not u sed by 1233 (83.6%) SSA vs 330 (40.4%) MENA patients (P < 0.001), respectively. Relative non-availability of diagnostic tests across both regions included adrenal antibo dies 63% vs 69.6% (P = 0.328), s-cortisol 49.4 % vs 26.7% (P = 0.004), s-ACTH 55.7% vs 53.3% (P = 0.217), and adrenal CT scans 52.4% vs 31.8% (P = 0.017) in the SSA and MENA region, respectively. Across the entire cohort, the overall hydrocortisone use and extrapolated proportion of synacthen use were 59.4% and 50.7%, respectively. Conclusions: Through the perception and practice of healthcare professional s, we identified significant challenges in the diagnosis and management of PAI wh ich may herald high mortality. Differences between regions may reflect the allocation of healthcare resources.